T117. PROMINENT AND PERSISTENT AUTISTIC TRAITS ARE ASSOCIATED WITH EARLY NON-REMISSION IN FIRST-EPISODE SCHIZOPHRENIA. (18th May 2020) - Pina-Camacho, Laura; Diaz-Caneja, Covadonga M; Fraguas, David; Boada, Leticia; Parellada, Mara; Winter-van Rossum, Inge; Kahn, Rene; Arango, Celso
Abstract: Background: Autistic phenotypic profiles in patients with schizophrenia are reportedly associated with poor outcomes, including higher odds of antipsychotic treatment failure. The Positive and Negative Syndrome Scale for Schizophrenia (PANSS) Autism Severity Scale (PAUSS) has been validated as a tool to identify "autistic profiles" in adolescents and adults with schizophrenia. We used the PAUSS (total score and subscores) to quantify autistic symptom load at different time points in a sample of patients with first episode schizophrenia (FES). We sought to investigate whether showing "prominent and persistent" autistic symptom load was associated with not achieving clinical remission at week 4 after the FES. Methods: We analysed a subsample of FES patients from the OPTiMiSE study that was treated with amisulpride in an open-label design and had completed 4 weeks of follow-up. The selected subsample was composed of 55 individuals (27.3% female, mean age 25.6 (6.2) years) at "high-risk of non-remission" at week 2; i.e. patients with schizophrenia (not schizophreniform nor schizoaffective disorder) that showed prominent and persistent baseline-to-2-week negative symptoms (PNS, using Galderisi et al 2013 definition) and that had not achieved clinical remission at week 2 (using Andreasen criteria). Results: In the selected subsample, the PAUSS showed acceptable internal consistency at baseline, 2-week, and 4-week visit (all Cronbach's alpha>0.7). Those with prominent (over the third tertile) and persistent (over the 4-week follow-up) PAUSS total scores, i.e. "autistic FES patients" had, relative to non-autistic FES patients, higher rates of comorbid social phobia (18.2% vs 0%, p= .041), higher PANSS positive, negative and total scores at week 2 and 4 (all p<.01), and a higher proportion of "non-remitters" at week 4 (91.7% vs 51.2%, p=.018). No other differences in demographic or clinical variables were found between both FES groups. Stepwise logistic regression analyses, controlling for potential confounders, revealed that showing a prominent and persistent "autistic phenotype" was associated with not achieving clinical remission at week 4 (B=2.148, OR=8.57, 95% CI= 1.01–73.5, p<0.05). Discussion: The delineation of "autistic profiles" with the PAUSS in the early stages of schizophrenia might enable early detection of subjects at higher risk of short-term antipsychotic treatment failure. It may also enable to explore the neurobiological underpinnings of particular phenotypic groups within schizophrenia, which might in turn help advance in the understanding of the pathophysiology and aetiology of psychosis.